Parent and Child Factors Predicting Early Intervention Choices of Australian Parents of Children With Autism Spectrum Disorder. Issue 2 (4th October 2019) - Carlon, Sarah; Carter, Mark; Stephenson, Jennifer; Sweller, Naomi
Abstract: Extant research addressing implicit factors related to intervention decisions made by parents of children with autism spectrum disorder (ASD) is limited and findings have been inconsistent. In the present study, 74 parents of preschoolers with ASD were surveyed regarding intervention use. The possible relationships between implicit parent factors (education level, age, causal beliefs about ASD, complementary and alternative medicine [CAM] use, and family income) and child factors (time since diagnosis, and perceived severity of ASD), and the number and type of interventions used were examined. Consistent with previous research, only a small number of significant relationships were found, including that family income, parent use of CAM, mother's education, parent belief in an unknown aetiology of ASD, and time since child's diagnosis were all related to the number of interventions used. Some specific findings of previous research were not replicated in the present study (e.g., neither beliefs in environmental aetiology of ASD nor parent education levels were related to the use of specific CAM interventions), indicating that factors affecting decision-making may not be consistent across samples. Nevertheless, future research including an expanded range of possible implicit factors with more diverse samples may provide a more accurate predictive model of parent decision-making.